Translating Buddhist Medicine in Medieval China, by C. Pierce Salguero - Helderman, Ira (Buddhist Studies Review, 2015)
Translating Buddhist Medicine in Medieval China, by C. Pierce Salguero, University of Pennsylvania Press, 2014. 256pp. Hb. $55.00/£36.00. ISBN-13: 9780812246117.